Keterampilan Belajar Mahasiswa di Masa COVID-19 - Birrul Walidaini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Student must be have study skill, for study and increase achievement study. This research was based on various problems were still many students who have not had a good study skill . The purpose of this research is to describe internet use for study skill. This research used a quantitative method of descriptive. The population of this research were students in IAIN Takengon. The sample of this research amount to 44 students, that selected by using random sampling technique. The instrument of the research was a Likert Scale. Data is analyzed with descriptive statistic. The research findings show that on general tudy skill is on quite well category.